PENGARUH KEPEMILIKAN INSTITUSIONAL, KUALITAS AUDIT, RETURN ON ASSET, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK - Auliana, Ratya Vica; Awaloedin, Dipateruna; Lubis, Reza Fahlevi (Universitas Trilogi, 2023)
Tax avoidance is an action taken intentionally to reduce the payment of tax obligations. This study aims to obtain empirical evidence regarding the effect of Institutional Ownership, Audit Quality, Return on Assets, and Leverage on Tax Avoidance. The sample used in this study is an agricultural company listed on the Indonesia Stock Exchange. The sampling technique was carried out by purposive sampling method which was used to select samples based on certain criteria, so that 75 samples were obtained from 15 companies during the last 5 years. The results of the study show that return on assets and leverage have a positive effect on tax avoidance. Meanwhile, audit quality has a negative effect on tax avoidance, and institutional ownership has no effect on tax avoidance.Keywords: Audit Quality; Institutional Ownership; Leverage; Return On Asset; Tax Avoidance.